2019
DOI: 10.13057/biodiv/d200233
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Beche-de-mers from Indonesia by molecular approach

Abstract: Abstract. Patantis G, Dewi AS, Fawzya YN, Nursid M. 2019. Identification of Beche-de-mers from Indonesia by molecular approach. Biodiversitas 20: 537-543. Sea cucumbers have been commercially traded around the world due to their nutritional values and health benefits. Sea cucumbers are marketed as processed sea cucumber, also known as beche de mer, teripang, haisen or gamat. Due to the high global demand of beche-de-mers, there have been several cases of fraud due to the visual shape and color similarities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 15 publications
0
13
0
5
Order By: Relevance
“…The present study gave different results that the golden sea cucumber obtained from Lombok island, West Nusa Tenggara was closer to S. horrens and S. monotuberculatus. The previous study showed that a phylogenetic tree constructed by the same method has successfully separated S. horrens, S. hermanni, and S. monotuberculatus (Patantis et al, 2019), which proved that the phylogenetic tree of COI sequences could also differentiate Stichopus at the species level.…”
Section: Identification Of Sea Cucumbermentioning
confidence: 80%
See 1 more Smart Citation
“…The present study gave different results that the golden sea cucumber obtained from Lombok island, West Nusa Tenggara was closer to S. horrens and S. monotuberculatus. The previous study showed that a phylogenetic tree constructed by the same method has successfully separated S. horrens, S. hermanni, and S. monotuberculatus (Patantis et al, 2019), which proved that the phylogenetic tree of COI sequences could also differentiate Stichopus at the species level.…”
Section: Identification Of Sea Cucumbermentioning
confidence: 80%
“…For the same reason, misidentification often occurs to differentiate between S. horrens, S. monotuberculatus, S. quadrifasciatus and S. naso (Purcell, Samyn, & Conand, 2012). Identification using the mitochondrial cytochrome c oxidase subunit I (COI) gene could distinguish several species in a specific genus of dried sea cucumber (Patantis, Dewi, Fawzya, & Nursid, 2019). Based on the previous studies above, molecular identification should be done to confirm the species of golden sea cucumber.…”
Section: Introductionmentioning
confidence: 99%
“…The appearance resembles with Terung from Kenjeran Waters, Surabaya, which showed similarity to Phyrella sp. [25].…”
Section: Resultsmentioning
confidence: 99%
“…Hewan invertebrata umumnya memiliki kesamaan morfologi yang tinggi antar spesies (cryptic), sehingga identifikasi molekuler dapat digunakan untuk memvalidasi spesies kriptik. Menurut Patantis et al (2019), secara molekuler, jenis-jenis teripang yang ada di perdagangkan di Indonesia adalah Acaudina sp., Actinopyga echinites, A. lecanora, A. miliaris, Bohadschia argus, B. marmorata, B. ocellata, B. vitiensis, Holothuria sp., H. atra, H. coluber, H. edulis, H. excellens, H. fuscocinerea, H. Rekonstruksi pohon filogenetik spesies-spesies yang ada dibandingkan dengan data GenBank ditampilkan pada Gambar 3.…”
Section: Pohon Filogenetikunclassified